О ПОЈЕДИНИМ БОГОСЛУЖБЕНИМ РУБРИКАМА ПСАЛТИРА С ПОСЛЕДОВАЊЕМ ГОРАЖДАНСКЕ ШТАМПАРИЈЕ (1521) (Prilozi za književnost, jezik, istoriju i folklor, 2024)
CONCERNING SOME LITURGICAL RUBRICS OF THE AUGMENTED PSALTER OF THE GORAŽDE PRINTING HOUSE (1521)This work deals with some liturgical rubrics, which were printed in the Augmented Psalter of the Goražde Printing House (1521). First of them predicts possible celebration of the Liturgy of Presanctified Gifts on Wednesday or Friday of Sunday of Cheese, if the feast day of St. Tryphon falls on one of these two days. The second rubric provides the chanting of the verses of the 17th Kathisma – the Amomos (Psalm 118) with refrain Hallelujah on the Great Saturday’s Orthros, but without the Egkomia. Taking into account the fact that hieromonk Theodor Ubavić was redactor for the process of printing the Augmented Psalter (1521) as well as the Služabnik or Leiturgikon (1519), and also the Prayer Book or Euchologium (1523) of the Goražde Printing House, these rubrics reveal his innovativity and in the same time deeply devotion to the Eastern Orthodox liturgical Tradition of Mount Athos, precisely of the Monastery Chilandari. Nevertheless, the already-mentioned rubrics represent the heritage of the older redaction of Typicon in the Eastern Orthodox Church, the so-called Stoudite synthesis, in comparing with the New Sabaite synthesis or Typicon of Great Lavra of St. Sava the Sanctified near Jerusalem. Above all, the results of our analysis definitely show that process of changing of the older layer of Typicon hasn’t been finished yet in the Athonite monasteries at the end of the 15th, and early in the 16th century.